The Leading Role of the Procurator in China's Plea Bargaining Process (Asian Journal of Social Science Studies, 2022)
The leniency system for plea bargaining in China is a plea bargaining system similar to plea bargaining in the United States. With the substantial increase in the application rate of the leniency system for plea guilty and accepting punishment, the criminal policy of "fewer arrests, careful prosecution and prudence" has become its due meaning. In China, the functions of censorship, arrest and prosecution are exercised by prosecutors. The burden of powers and responsibilities of prosecutors allows prosecutors to have procedural decision-making power and substantive disposition power in the plea bargaining process, that is, the procuratorial dominance. In the context of fewer arrests, prudent prosecution and prudent detention, prosecutors have greater discretion over arrest and prosecution during the plea negotiation process, coupled with the high adoption rate of sentencing suggestions in practice, the expansion of prosecutors’ substantive disposition powers, and the procuratorial dominance further highlighted. However, we must clarify the relationship between procuratorial power and sentencing power, clarify the status and responsibilities of prosecutors, and further improve the leading role of prosecutors.